2021
DOI: 10.1177/10547738211035456
|View full text |Cite
|
Sign up to set email alerts
|

A Heideggerian Phenomenological Study of the Lived Experiences of Ghanaian Patients Living With End-Stage Renal Disease

Abstract: There is a lack of knowledge regarding perceptions, feelings, and experiences of Ghanaian patients living with ESRD. This study aimed to discover the experience and meaning of living with ESRD. This qualitative study was conducted using Heideggerian hermeneutic phenomenology. A total of 13 participants were purposefully selected, and data was collected through individual semi-structured interviews. The recorded interviews were transcribed and analyzed using Diekelmann, Allen, and Tanner method. After the final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 37 publications
4
1
0
Order By: Relevance
“…Participants frequently chose to reduce the number of hemodialysis sessions per week, skipped taking their prescribed medications and sold their properties due to financial limitations. This finding is consistent with studies conducted in Nigeria, Ethiopia, Ghana, Jordan and the US [ 22 , 25 , 33 , 34 , 36 ]. There is a need for the Federal Ministry of Health to increase the number of government-funded dialysis centers and monitor the cost and quality of renal services provided in the country to reduce the arbitrary prices for dialysis seen in private dialysis facilities.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Participants frequently chose to reduce the number of hemodialysis sessions per week, skipped taking their prescribed medications and sold their properties due to financial limitations. This finding is consistent with studies conducted in Nigeria, Ethiopia, Ghana, Jordan and the US [ 22 , 25 , 33 , 34 , 36 ]. There is a need for the Federal Ministry of Health to increase the number of government-funded dialysis centers and monitor the cost and quality of renal services provided in the country to reduce the arbitrary prices for dialysis seen in private dialysis facilities.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, a systematic review reported that spirituality enables hemodialysis patients to give value to their lives and feel strong while dealing with this challenging disease [ 32 ]. A similar study performed in Ghana is also consistent with our findings in that participants exhibited spiritual fluctuation (belief in God and slips of faith) [ 33 ]. They described belief in God as a means of accepting and coping with the disease.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For example, one study investigated social stigma among patients with ESRD, who were at times reticent to draw excessive attention to their dietary needs/fluid intake restrictions and avoided disclosing their disease to others [17]. Moreover, patients with ESRD have reported stigmatization after specific events, including refusals to eat together and facing unsupportive or unhelpful attitudes from health workers [18].…”
Section: Introductionmentioning
confidence: 99%